Evaluation of Knowledge on Complete Denture Fabrication: A Cross-Sectional Study among Fourth-Year Dental Students at Gharyan University - Rokiya Alshaibi,; Nesrin Belaid, (AlQalam Journal of Medical and Applied Sciences, 2025)
Complete dentures remain an essential treatment option for edentulous patients, especially in regions where implant-supported prostheses are limited. Successful prosthodontic outcomes require systematic execution of clinical steps, including patient examination, impression taking, custom tray fabrication, jaw relation recording, try-in, and post-insertion management. This study aimed to assess the knowledge of complete denture fabrication among fourth-year dental students. A descriptive cross-sectional design was employed among 37 students (94.9% response rate) enrolled in 2024 at the Department of Prosthodontics, Faculty of Oral and Dental Medicine, Gharyan University. Data were collected using a validated, self-administered questionnaire covering patient assessment, primary and final impressions, custom tray design, jaw relation records, occlusal plane orientation, articulator use, try-in procedures, and post-insertion care, and analyzed descriptively. All students (100%) reported performing histories, oral examinations, primary impressions with alginate, and centric relation registration. Knowledge gaps were observed in advanced procedures: 75.7% selected light-cure acrylic for custom trays, awareness of spacers, stops, and relief holes was limited, polyvinylsiloxane was the most frequently used final impression material (62.2%), yet 59.5% disinfected impressions improperly with water alone. None used a face bow or semi-adjustable articulators, relying solely on non-adjustable types. Students demonstrated solid foundational knowledge of basic procedures; however, deficiencies in custom tray design, post-palatal seal determination, impression disinfection, and articulator use indicate a need for enhanced clinical teaching and practical training to meet current prosthodontic standards.